An analysis of consumer purchasing behavior for luxury goods on the social and e-commerce platform : a case study of red - Jiang, Shan; Sununta Siengthai; Vimolwan Yukongdi; Zimmermann, Willi; China Scholarship Council (CSC) (2020)
Nowadays, China's rapidly changing Internet technology and the rapid popularization of e-commerce have driven the rise of domestic luxury online consumption. With its efficient resource integration and scale advantages, luxury e-commerce platforms are gradually becoming the mainstream trend of luxury online transactions. At present, sharing, interaction, and social networking have become essential elements of the Internet platform. More and more consumers tend to learn from the users on the Internet to share the product information they need and make shopping decisions. This article divides the sharing of community application users into four dimensions, and studies how they influence consumers' willingness to purchase through user-generated content (UGC), perceived usefulness and para-social interaction. It uses the RED platform as a case study. This research uses the quantitative analysis research method. About 250 questionnaires were obtained via online channel. Then, the data were analyzed and presented using descriptive analysis, reliability and factor analysis, and structural equation modeling (SEM) to draw relevant conclusions and recommendations. The findings suggest that UGC, perceived usefulness, and para-social interaction are significantly and positively related to consumer purchase intention. As a product of UGC in the new media environment, RED has the dual identities of the e-commerce platform and social platform. Studying the communication characteristics of RED can explore the influence of media in the Internet era on social interaction and the changes brought to the consumer environment. Provide new ideas for future Internet consumption and socializing.
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M. BA.) - Asian Institute of Technology, 2020
Keywords: Consumer behavior -- China -- Case studies; Electronic commerce -- China -- Case studies